2007
DOI: 10.1186/1477-7827-5-31
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2-alpha receptor (FPr) expression on porcine corpus luteum microvascular endothelial cells (pCL-MVECs)

Abstract: Background: The corpus luteum (CL) is a transient endocrine gland and prostaglandin F2-alpha is considered to be the principal luteolysin in pigs. In this species, the in vivo administration of prostaglandin F2-alpha induces apoptosis in large vessels as early as 6 hours after administration. The presence of the prostaglandin F2-alpha receptor (FPr) on the microvascular endothelial cells (pCL-MVECs) of the porcine corpus luteum has not yet been defined. The aim of the study was to assess FPr expression in pCL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Although FPr mRNA has been demonstrated to be expressed in cultured LECs isolated from the CLs of cycling pigs [39] and cows [9], some studies have reported the absence of FPr in bovine LECs isolated from pregnant CLs [7,40]. The differences observed in FPr mRNA expression may be due to differences in the physiological stages of the CL, culture systems, types of LEC or immunostaining techniques as described previously.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although FPr mRNA has been demonstrated to be expressed in cultured LECs isolated from the CLs of cycling pigs [39] and cows [9], some studies have reported the absence of FPr in bovine LECs isolated from pregnant CLs [7,40]. The differences observed in FPr mRNA expression may be due to differences in the physiological stages of the CL, culture systems, types of LEC or immunostaining techniques as described previously.…”
Section: Discussionmentioning
confidence: 85%
“…The differences observed in FPr mRNA expression may be due to differences in the physiological stages of the CL, culture systems, types of LEC or immunostaining techniques as described previously. FPr protein has recently been identified on cultured porcine LECs [39]. However, the presence of functional FPr in LECs isolated from bovine CLs has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since PGF 2a also augmented the content of CREB in CL of early pregnant pigs, it seems likely that PGF 2a is responsible for enhancement of cAMP action, and can also increase availability of CREB which is activated further by luteotropic hormones acting via cAMP, e.g., PGE 2 and LH. While expression of PTGFR was prominent in endothelial cells (Zannoni et al 2007) of cyclic CL, we postulate that PGF 2a might also be engaged in luteal function maintenance during early pregnancy in pigs by stimulation of angiogenesis. A positive effect of PGF 2a on angiogenesis was previously demonstrated in bovine CL (Shirasuna et al 2012, Zalman et al 2012.…”
Section: Rescue Of Luteal Function During Early Pregnancymentioning
confidence: 99%
“…gyrB was used to normalize for transcript quantification, because it has been shown to be not affected by cell density and/or agr (13). Relative RNAIII expression was calculated as the differences in cycle thresholds (⌬C T ) (gyrB C T Ϫ RNAIII C T ) for all samples as previously described (25,47,53). PCR experiments were performed using two biological replicates, each tested in triplicate.…”
Section: Methodsmentioning
confidence: 99%